The State, Ulayat Rights, and Forest Conversion: Opportunities for the Talang Mamak Community? - Firmanda, Hengki; Nurbani, Erlies Septiana; Wafi, Mahmud Hibatul; Samariadi; Manik, Rahmat GM; Supaat, Dina Imam (Jambe Law Journal, 2025)
This study examines the potential reclassification of forest areas from National Park status to customary land (ulayat) for the Talang Mamak indigenous community in Riau. The issue stems from a longstanding conflict between the government and the Talang Mamak people, who feel that their traditional rights to the forest have been seized by the state through conservation policies. The research is positioned as a critique of the misalignment between state environmental policies and the recognition of indigenous rights, particularly in the management of natural resources. The research method used is a juridical-sociological approach, combining policy analysis through literature review and field interviews to gather perspectives from the indigenous community, as well as legal frameworks related to customary land rights and forest management. The findings show that the state’s centralized, conservation-oriented policies often conflict with sustainable forest management practices that the Talang Mamak people have followed for centuries. This conflict is exacerbated by the weak recognition and legal protection of the community's customary land rights. However, there is significant potential to reclassify the forest into indigenous-managed areas, provided there is strong policy support and active participation from all relevant stakeholders